Automatic Milkfish Feeding System Based on Fuzzy Logic on Microcontroller - Fadhiel Fadhiel Naufal Huda; Silvester Ariski Tobi; Fadhiel Naufal Huda; Khoirul Kodri Nasution; Muhamad Ariq Maulana; Hanatasya Ramadhan; Ahmad Fahrezzi; Nailah Azzahra Cinthari; Willa Wulandari; Bunga Ligar Balebat; Muhammad Rayhan Kurniawan; Stilo Farrel Ticoalu; Muhammad Faiz Assariy (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
Dear Editorial Team, I hope this message finds you well. Please find attached our manuscript entitled "Automatic Milkfish Feeding System Based on Fuzzy Logic on Microcontroller", which we would like to submit for possible publication in Journal of Applied Science, Technology & Humanities. This paper presents our research on automatic feeding system was designed using fuzzy logic and a microcontroller to adaptively adjust milkfish feed based on water temperature, with the aim of improving feed efficiency and supporting sustainable aquaculture. We believe that our findings could contribute significantly to the field of aquaculture management. The manuscript has not been published elsewhere and is not under consideration by any other journal. Please let us know if any additional information is required. We look forward to your feedback. Thank you for your time and consideration. Best regards,Fadhiel Naufal HudaIPB Universityfadhielnaufal@apps.ipc.ac.id